2023
DOI: 10.1155/2023/8435480
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Advanced Metal-Oxide Nanocomposites for Effective and Low-Cost Antimicrobial Activates: A Review

Abstract: Pathogens with multidrug resistance have recently been responsible for widespread disease, fatalities, and economic distress. A nanomaterial with antibacterial characteristics is used to reduce the infection’s resistance. Metal-oxide nanocomposites are nanomaterials that exhibit outstanding physical and chemical characteristics. They are prime candidates for innovative functional materials with antimicrobial activity as one of their main uses. This review will summarize the current progress on the antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 131 publications
0
7
0
Order By: Relevance
“…In terms of the antibacterial properties of the nanomaterials, the ability of the bacterial cells to regrow on the nutrient agar plates following their incubation on the MIC assay shows that the Cu-TiO 2 nanoparticles are bacteriostatic, and not bactericidal (i.e., they inhibit bacterial growth without killing the cells. , The clinical importance of bactericidal and bacteriostatic samples, however, is still under dispute and is not used to rule out the potential application of samples as antimicrobial agents. In general, the results in Figure a,b have shown that no significant differences in the antimicrobial activity of the TiO 2 nanoparticles were observed in the presence and the absence of copper.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the antibacterial properties of the nanomaterials, the ability of the bacterial cells to regrow on the nutrient agar plates following their incubation on the MIC assay shows that the Cu-TiO 2 nanoparticles are bacteriostatic, and not bactericidal (i.e., they inhibit bacterial growth without killing the cells. , The clinical importance of bactericidal and bacteriostatic samples, however, is still under dispute and is not used to rule out the potential application of samples as antimicrobial agents. In general, the results in Figure a,b have shown that no significant differences in the antimicrobial activity of the TiO 2 nanoparticles were observed in the presence and the absence of copper.…”
Section: Resultsmentioning
confidence: 99%
“…This cost-effective simple synthesis strategy can be useful as a platform to preparation of various metal—metal oxide nanostructured materials for in particular targeted biomedical applications for example, as contrast agents when introducing magnetite into their composition [ 4 ]. Bactericide-containing colloidal heterodimer nanomaterials may be use as antibacterial agents to address the ever-increasing problem of antibiotic-resistant bacteria [ 86 ]. At the same time, the presence of a stabilizing polymer in the obtained composites, which has easily modifiable carboxyl (anhydride) groups, makes it possible to introduce additional amine-containing antibiotic substances into the composition of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, scientists have embarked on the development of exceptionally potent drugs capable of combating a diverse array of bacterial systems, thereby making it exceedingly arduous for bacteria to develop resistance mechanisms. One promising strategy to address the shortcomings of traditional antibiotics is the integration of antimicrobial nanoscale materials ( Birhanu et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%